Therapeutic treatment of New Zealand mouse disease by a limited number of anti-idiotypic antibodies conjugated with neocarzinostatin. - Harata, N (1990)
-81 and NE-1 idiotypes (Id) of human nephritogenic anti-DNA antibodies are interspecies Id expressed also in NZB/W F1 mice. We tried to manipulate the synthesis of spontaneously occurring anti-DNA antibody using monoclonal anti-Id antibodies (D1E2 and 1F5) conjugated with a cytotoxic agent, neocarzinostatin (NCS). In vivo administration of anti-Id antibodies conjugated with NCS brought about an improvement in the survival rate of female NZB/W F1 mice. It also caused a retardation of development of lupus nephritis and decreased the numbers of anti-DNA-producing cells. The suppression of anti-DNA antibody synthesis was specific and Id-mediated. The results indicate that the use of a limited number of anti-Id antibodies in combination with a cytotoxic agent may be applicable therapeutically to autoimmune diseases.